2011
DOI: 10.17305/bjbms.2011.2622
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone remodelling parameters after one year treatment with alendronate in postmenopausal women with osteoporosis

Abstract: Antiresorptive agents are widely used to treat osteoporosis. Both reduction in bone turnover and increase in BMD may be necessary to decrease the fracture risk. The aim of the study was to evaluate the effects of aledronate on bone turnover markers and bone mineral density in postmenopausal women with osteoporosis. The study involved a group of 56 postmenopausal women with osteoporosis treated with alendronate (70 mg) weekly at the Institute of Nuclear Medicine Clinical Center University of Sarajevo during a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Under pathological stimulation, osteoclast activity is enhanced, which results in the degradation of large amounts of type-I collagen to CTX-Ⅰ in the blood. The physiological variation of CTX-Ⅰ in serum is small and could reflect bone resorption specifically [ 45 ]. The increase in serum levels of CTX-I and TRACP-5b indicated that low phosphorus intake caused hens to mobilize calcium and phosphorus in bone to support eggshell formation.…”
Section: Discussionmentioning
confidence: 99%
“…Under pathological stimulation, osteoclast activity is enhanced, which results in the degradation of large amounts of type-I collagen to CTX-Ⅰ in the blood. The physiological variation of CTX-Ⅰ in serum is small and could reflect bone resorption specifically [ 45 ]. The increase in serum levels of CTX-I and TRACP-5b indicated that low phosphorus intake caused hens to mobilize calcium and phosphorus in bone to support eggshell formation.…”
Section: Discussionmentioning
confidence: 99%